1986
DOI: 10.1029/ja091ia10p11019
|View full text |Cite
|
Sign up to set email alerts
|

The resolved layer of a collisionless, high β, supercritical, quasi‐perpendicular shock wave: 1. Rankine‐Hugoniot geometry, currents, and stationarity

Abstract: A comprehensive set of experimental observations of a high β (2.4), supercritical (Mf = 3.8), quasi‐perpendicular (ΘBn1 ∼ 76°) bow shock layer is presented, and its local geometry, spatial scales, and stationarity are assessed in a self‐consistent, Rankine‐Hugoniot‐constrained frame of reference. Included are spatial profiles of the ac and dc magnetic and electric fields, electron and proton fluid velocities, current densities, electron and proton number densities, temperatures, pressures, and partial densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
190
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(218 citation statements)
references
References 50 publications
26
190
2
Order By: Relevance
“…Moving from right (upstream of the enhancement) to left (through the enhancement): upstream of the leading edge, the magnetic field direction is within 45 • of the model bow shock normal; across the leading edge θ Bn rises, with a slight plateau at the end of the sharp ramp, then rises more quickly to a value near 90 • within the enhancement. The magnetic field magnitude at Cluster 2 has a feature similar to a shock foot, typically observed at quasiperpendicular shocks (e.g Scudder et al, 1986). Cluster 3 sees a similar feature, but it is less pronounced, and Cluster 4 and 1 observe short ramps, lasting for about 0.5 s, on the leading edge.…”
Section: Overviewmentioning
confidence: 83%
See 1 more Smart Citation
“…Moving from right (upstream of the enhancement) to left (through the enhancement): upstream of the leading edge, the magnetic field direction is within 45 • of the model bow shock normal; across the leading edge θ Bn rises, with a slight plateau at the end of the sharp ramp, then rises more quickly to a value near 90 • within the enhancement. The magnetic field magnitude at Cluster 2 has a feature similar to a shock foot, typically observed at quasiperpendicular shocks (e.g Scudder et al, 1986). Cluster 3 sees a similar feature, but it is less pronounced, and Cluster 4 and 1 observe short ramps, lasting for about 0.5 s, on the leading edge.…”
Section: Overviewmentioning
confidence: 83%
“…Magnetic field observations typically show a short ramp in |B|, possibly with a "foot" ahead of the ramp, an overshoot after the ramp, or a high frequency wave train upstream of the ramp (e.g. Scudder et al, 1986). Quasiperpendicular shocks have been studied in detail over many years and recently Cluster data have been used to examine…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties are associated with interpreting differences between multipoint spacecraft measurements when only a few spatial scales can be observed and the fact that the conversion from time to space in the data relies on knowledge of the shock speed relative to the observation points. The separation between macrostructure and microstructure was already considered in an influential two-spacecraft study using International Sun-Earth Explorer (ISEE) data, where it was found that, by using inter-correlation with different averaging periods, the correlation between the two spacecrafts decreased strongly when the averaging period was approximately 0.15 times the upstream proton gyroperiod (Scudder et al 1986). The inference is that fluctuations seen at short time scales are associated with non-stationarity, or the breakdown of the usual assumption of one-dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…However, the profiles become steeper with the increase of the Mach number [6] so that the conditions for demagnetization may be achieved more easily. The transition layer of quasi-perpendicular non-relativistic shocks consists of several distinct regions [7], the steepest magnetic field increase is a "ramp" (whose width is less than the ion inertial length l i = c/ω pi , ω 2 pi = 4πn u e 2 /m i ) and a large magnetic overshoot (whose width is of the order of the downstream ion gyroradius). The overshoot height is found experimentally to increase with the increase of the Mach number [8].…”
Section: Introductionmentioning
confidence: 99%